Lateral and vertical juxtaposition of matrix‐rich and matrix‐poor lithologies caused by particle settling in mixed mud–sand deep‐marine sediment suspensions. Issue 3 (16th October 2018) - Angus, Katrina; Arnott, Robert William Charles; Terlaky, Viktor
Abstract: Sandy sedimentary rocks rich in detrital matrix (>10% silt/clay) have long been recognized in the ancient sedimentary record, and nowhere more commonly than in deep‐marine turbidite systems. Despite this, their depositional mechanisms remain poorly understood, in part because these rocks, which are enriched in fine‐grained sediment, are often poorly exposed in outcrop or are confined to observation in core. Matrix‐rich strata in the Neoproterozoic Windermere Supergroup, in contrast, are very well‐exposed and show systematic changes in lithofacies over distances of several tens to a few hundreds of metres along‐strike. Notably, these strata are observed in both basin floor and continental slope deposits, suggesting that their occurrence and systematic lithological arrangement is related to mechanistic, rather than palaeogeographic, controls. Specifically, the facies transect consists of structureless, clayey sandstone that transforms along‐strike to a two‐layer deposit with the development of an upper, planar‐based, markedly more matrix‐rich layer. Further along‐strike, the basal clayey sandstone thins and eventually pinches out, leaving only the (upper) sandy claystone layer, which in turn thins along‐strike and then pinches out. These systematic changes in lithology, but more specifically the distribution of clay, is interpreted to form a depositional continuum related to particle settling in a horizontally advecting, high concentration particle suspension formed along the margins of an avulsion‐related high‐energy turbulent suspension.